Beneficial Effects of Anisodamine in Shock Involved Cholinergic Anti-Inflammatory Pathway - Zhao, Ting; Li, Dong-Jie; Liu, Chong; Su, Ding-Feng; Shen, Fu-Ming (Frontiers in Pharmacology, 2011)
Anisodamine, an antagonist of muscarinic receptor, has been used therapeutically to improve blood flow in circulatory disorders such as septic shock in China since 1965. The main mechanism of anisodamine for anti-shock proposed in Pharmacology for Chinese medical students is to improve blood flow in the microcirculation. Here, we suggest a new mechanism for its anti-shock effect. That is, anisodamine, by blocking muscarinic receptor, results in rerouting of acetylcholine to alpha7nAChR bringing about increased acetylcholine-mediated activation of alpha7nAChR and the cholinergic anti-inflammatory pathway.